2020
DOI: 10.1111/nph.16741
|View full text |Cite
|
Sign up to set email alerts
|

GDSL lipase occluded stomatal pore 1 is required for wax biosynthesis and stomatal cuticular ledge formation

Abstract: The plant leaf surface is coated with a waterproof cuticle layer. Cuticle facing the stomatal pore surface needs to be sculpted to form outer cuticular ledge (OCL) after stomatal maturation for efficient gas exchange. Here, we characterized the roles of Arabidopsis GDSL lipase, Occlusion of Stomatal Pore 1 (OSP1), in wax biosynthesis and stomatal OCL formation. OSP1 mutation results in significant reduction in leaf wax synthesis and occlusion of stomata, leading to increased epidermal permeability, decreased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 62 publications
10
63
0
Order By: Relevance
“…The only glossy gene that was unaffected by the gl3 induction is gl13 , which is an ABC transporter functioning in the secretion of cuticular waxes across the plasma membrane (Li et al, 2013a). Besides the known glossy genes, 86 additional genes were up-regulated by the dTALes including six genes encoding 3-ketoacyl-CoA synthases (KCS) as gl4 does (Liu et al, 2009), two genes encoding HXXXD-type acyltransferase related proteins similar to gl2 (Tacke et al, 1995), three genes encoding GDSL esterase/lipase proteins, which was reported to be involved in wax biosynthesis (Tang et al, 2020), and two genes encoding aldehyde dehydrogenases ( Supplemental Data Set 1 ). The 54 down-regulated genes were identified in both dT1 and dT2 comparisons with the EV group, which do not include any known glossy genes.…”
Section: Resultsmentioning
confidence: 99%
“…The only glossy gene that was unaffected by the gl3 induction is gl13 , which is an ABC transporter functioning in the secretion of cuticular waxes across the plasma membrane (Li et al, 2013a). Besides the known glossy genes, 86 additional genes were up-regulated by the dTALes including six genes encoding 3-ketoacyl-CoA synthases (KCS) as gl4 does (Liu et al, 2009), two genes encoding HXXXD-type acyltransferase related proteins similar to gl2 (Tacke et al, 1995), three genes encoding GDSL esterase/lipase proteins, which was reported to be involved in wax biosynthesis (Tang et al, 2020), and two genes encoding aldehyde dehydrogenases ( Supplemental Data Set 1 ). The 54 down-regulated genes were identified in both dT1 and dT2 comparisons with the EV group, which do not include any known glossy genes.…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis by TEM indicated that the cuticle layer of atmin7 was much thinner than the WT plants ( Figure 3 a). The cuticular ledge is the outermost layer of the stomata pore, which regulates stomatal function [ 43 , 44 ]. TEM also demonstrated that the cuticular ledge of stomata in atmin7 leaves was almost missing ( Figure 3 b).…”
Section: Resultsmentioning
confidence: 99%
“…Pto proliferates significantly and causes disease following entry into the plant apoplast through natural openings, such as stomata and wounds [45]. In addition to leaf surfaces, cutin also forms a ledge on guard cells of stomata that supports their proper structure and function [43,44]. The atmin7 mutant plants exhibited impaired stomata and defective stomata cuticular ledge.…”
Section: The Roles Of Plant Cuticle During Plant-pathogen Interactionmentioning
confidence: 99%
“…In this issue of New Phytologist , Tang et al . (2020; pp. 1880–1896) have identified a novel Arabidopsis thaliana mutant osp1 ( occluded stomatal pore 1 ) that has disrupted synthesis of cuticular waxes and shows structural alterations to the stomatal cuticular ledge.…”
Section: Plants Lacking Osp1 Have Altered Wax Composition and Occludementioning
confidence: 99%
“…The ability to quickly close these pores or in the longer-term to adapt stomatal density in response to environmental conditions such as drought is well documented, but less is known about whether plants alter their cuticle composition to regulate water loss, and if such changes occur in an epidermal cell typespecific way (Holroyd et al, 2002). In the recently published article in New Phytologist, Tang et al (2020;doi: 10.1111/nph.16741) have identified a novel Arabidopsis thaliana mutant osp1 (occluded stomatal pore 1) that has disrupted synthesis of cuticular waxes and shows structural alterations to the stomatal cuticular ledge. This phenotype, which is reminiscent of the previously described fused outer cuticular ledge mutant (focl1; Hunt et al, 2017), has effects on both stomatal and nonstomatal water losses.…”
mentioning
confidence: 99%